Home door security system based on Internet of Things - Tri Ananda Muhammad, Vajrel; Hamdani (Journal of Industrial Automation and Electrical Engineering, 2024)
The development of technology in the digital era has a significant impact in various fields including home security. The existence of conventional door locks that are easily broken into and the risk of losing physical keys raises the need for a more sophisticated security system. This research aims to design an Internet of Things (IoT)-based home door security system that utilizes the Telegram application as a remote control medium. The system integrates a fingerprint sensor, keypad, and push button to open and close the door. Passive Infrared Receiver (PIR) sensor and ESP32-CAM to detect motion and take pictures that are sent to Telegram. In addition, the system is equipped with an Uninterruptible Power supply (UPS) to ensure the device remains operational during a power outage. The results show that the electronic door lock system works well. The motion detection system is also able to accurately detect activity around the door and send images to Telegram with a fast response time. In addition, the use of UPS to keep the system functioning despite the interruption of electricity supply proved to be effective. Based on the test results, it can be concluded that this IoT-based home door security system is effective, easy to use, responsive, and continues to function despite a power outage